The Testament of Diego de Guevara (c. 1450-1520) (BSAA arte, 2019)
Diego de Guevara (c. 1450-1520), an illustrious Spaniard settled in Flanders, occupied a prominent place in the Habsburg court, as ambassador of Philip the Fair, Margaret of Austria and Charles V. But he had also an important art collection, with paintings such as the Arnolfini Portrait of Jan van Eyck. The present article analyzes and transcribes in the final annex an unpublished document: his testament. Likewise, new information is provided, such as the one that leads to modify the date of birth of his son Felipe, known above all for his Commentary on painting and ancient painters.
Keywords: Diego de Guevara; testament; Flemish painting